Answer:
Step-by-step explanation:
We have to find the equation of plane that is parallel to the vectors
![\langle 3,0,3\rangle, \langle0,1,3\rangle](https://tex.z-dn.net/?f=%5Clangle%203%2C0%2C3%5Crangle%2C%20%5Clangle0%2C1%2C3%5Crangle)
The plane also passes through the point (2,0,-1).
Hence, the equation of plane s given by:
![\displaystyle\left[\begin{array}{ccc}x-2&y-0&z+1\\3&0&3\\0&1&3\end{array}\right]\\\\=(x-2)(0-3) - (y-0)(9-0) + (z+1)(3-0)\\=-3(x-2)-9y+3(z+1)\\\Rightarrow -3x + 6 - 9y + 3z + 3 = 0\\\Rightarrow 3x + 9y -3z -9 = 0\\\Rightarrow x + 3y -z - 3 = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx-2%26y-0%26z%2B1%5C%5C3%260%263%5C%5C0%261%263%5Cend%7Barray%7D%5Cright%5D%5C%5C%5C%5C%3D%28x-2%29%280-3%29%20-%20%28y-0%29%289-0%29%20%2B%20%28z%2B1%29%283-0%29%5C%5C%3D-3%28x-2%29-9y%2B3%28z%2B1%29%5C%5C%5CRightarrow%20-3x%20%2B%206%20-%209y%20%2B%203z%20%2B%203%20%3D%200%5C%5C%5CRightarrow%203x%20%2B%209y%20-3z%20-9%20%3D%200%5C%5C%5CRightarrow%20x%20%2B%203y%20-z%20-%203%20%3D%200)
It is the required equation of plane.
Here, 3t - 7 = 5t
5t - 3t = -7
2t = -7
t = -7/2
Then, 6t = 6(-7/2) = 3(-7) = -21
In short, Your Answer would be -21
Hope this helps!
It would be a negative number due to the fact that there are three negative numbers. A negative times a negative makes a positive, so because there are three it means the negative won't cancel out.
Answer:
Part A: one solution:
Part B: x = 3, y = 4.
1) Part A: how many solutions does the pair of equations for lines A and B have?
The solution of a system of equations in a graph is given by the intersetion of the curves that represent the equations.
In this case, there are two straight lines, which intersect in one and only one point.
Hence, the system has one solution.
2) Part B: what is the solution to the equations of lines A and B?
The solution is the pair of coordinates of the intersection point. It is (3, 4).
Therefore, the solution is x = 3, y = 4.
Step-by-step explanation:
MRK ME BRAINLIEST PPLLZZZZZZZZZZZZZZZZZZZ
It's simple, just subtract 3 from 6 because the have the same terms and variables then keep your answer as it should be. you should get 4b³c²+3b²c³